2016
DOI: 10.1371/journal.pone.0158673
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive MR Urography Protocol: Equally Good Diagnostic Performance and Enhanced Visibility of the Upper Urinary Tract Compared to Triple-Phase CT Urography

Abstract: ObjectivesTo prospectively compare the diagnostic performance and the visualization of the upper urinary tract (UUT) using a comprehensive 3.0T- magnetic resonance urography (MRU) protocol versus triple-phase computed tomography urography (CTU).MethodsDuring the study period (January-2014 through December-2015), all consecutive patients in our tertiary university hospital scheduled by a urologist for CTU to exclude UUT malignancy were invited to participate. Diagnostic performance and visualization scores of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 22 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…There are several techniques to improve opacification and distention of urinary tracts in CTU, including oral and intravenous hydration, use of compression belts and administration of diuretics [1, 2, 8, 20, 31, 32]. Also, reduction of contrast layering effect may result in improving diagnostic accuracy of CTU [17, 20, 33]. It is highlighted in evaluation of ureters in adults, where suboptimal distention and peristaltic waves may limit visualization of small urothelial tumors [32, 34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several techniques to improve opacification and distention of urinary tracts in CTU, including oral and intravenous hydration, use of compression belts and administration of diuretics [1, 2, 8, 20, 31, 32]. Also, reduction of contrast layering effect may result in improving diagnostic accuracy of CTU [17, 20, 33]. It is highlighted in evaluation of ureters in adults, where suboptimal distention and peristaltic waves may limit visualization of small urothelial tumors [32, 34].…”
Section: Discussionmentioning
confidence: 99%
“…However, usefulness of furosemide has been assessed in a very limited manner. Also, it is highlighted that increased diuresis caused by furosemide may increase distention of the urinary tract and reduce contrast medium (CM) concentration, resulting in decreased opacification and poorer visualization of the collecting system [17].…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that as compared to CTU, MRU is efficient in differentiating between the lower and upper poles of the kidneys [ 35 ]. As compared to CTU, MRU is likely to become the primary investigation technique in the selected patients because it does not entail exposure to radiation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…MR urography is used to image the upper tracts and is recommended by multiple guidelines as an alternative to CT urography when necessary such as the AUA, European Association of Urology (EAU), and NCCN [ 29 ]. One small prospective study of 20 patients showed equal diagnostic performance between 3T MR urography and triple phase CT urography obtained to exclude upper tract malignancy [ 29 ]. Visualization scores noted CT urography to have slightly better visualization of the intrarenal cavity and poorer visualization of the distal ureters, and MR urography showing slightly better visualization of the ureters.…”
Section: Role Of Imaging In Stagingmentioning
confidence: 99%